Transparansi Pengelolaan Alokasi Dana Desa Dalam Pembangunan Di Desa Dasan Borok Kecamatan Suralaga Kabupaten Lombok Timur - Muhamad Juaini; Danang Prio Utomo (Universitas Hamzanwadi, 2023)
This study aims to determine the form of transparency carried out by the village government in managing the allocation of village funds (ADD). This study uses a qualitative method. Data obtained through observation, interviews and documentation. The data is then analyzed by reducing the data, presenting the data and drawing conclusions. The results of this study indicate that at the planning stage the Dasan Borok Village government applies the principle of transparency by holding deliberation by inviting various parties such as the village government, village institutions, village consultative bodies (BPD), religious leaders, community leaders and so on. In the deliberation, the village government conveyed in detail the amount of funds received, the sources of funds, and the planned use of these funds. The form of transparency at the implementation stage is by installing billboards and activity boards that contain an overview of the activities and the funds used. The form of transparency in the accountability stage is by making several reports such as the village government accountability statement report. reports on the implementation of village governance, reports on the realization of the implementation of APBDes accountability, and reports on stunting convergence. These reports are then submitted to the PMD Office, Inspectorate and BPD. This means that the Dasan Borok Village government manages the allocation of village funds (ADD) properly and transparently at every stage.